Influence of Spanish as a First Language in the Learning Process of English as a Foreign Language in the School of Hospitality and Tourism at PUCE Esmeraldas, 2017 - Rúa Castillo, Arlet Yamel (2018)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés